Cultivation of amniotic fluid in patients undergoing cesarean section at (Ex-HML) Maternal Perinatal Institute. - Shigyo, Gabriela (2015)
The study objectives were to identify the most common germs in amniotic fluid of patients undergoing cesarean section and its relation to the integrity of the membranes. A prospective study of 100 patients undergoing selected by simple random method cesarean section was performed. Amniotic fluid sample was taken under sterile conditions during surgery and cultivated in aerobic and anaerobic media. 21% positive cultures, of which 90% were in patients with ruptured membranes and 10% was found with intact membranes. The germs found were Acinetobacter sp 38.1 0% and 28.57% Staphylococcus aureus. 52.6% positive cultures corresponded to break membranes less than 6 hours. We conclude that the most common organisms isolated from the amniotic fluid of patients cesarean are unlike aerobics foreign studies. The finding of 52.6% of positive cultures from patients with ruptured membranes less than 6 hours, differs from current management schemes antibiotics from 6 o'clock. The cases of positive cultures with intact membranes, would relate to other routes of contamination of amniotic fluid, which merit further study.